Learning History in Postcolonial Philippines: An Analysis of Cesar A. Majul's "Moro Wars" and Philippine Historiography - OZAKI, MARIKO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Nation-building has been a central agenda in writing and learning Philippine history ever since the country's independence. History has served to construct the national identity which has eagerly been pursued in postcolonial society, and nationalism has remained a guiding principle of historical experiences. This paper takes a look at Cesar Majul's historiography as an example of nationalist history and analyzes Majul's construction of the well-known "Moro War" thesis and its influence in the broader socioeconomic context. Such "nationalist history", has been criticized by various schools of history, such as postcolonial, subaltern, autonomous history, and the current academic fashion of postmodernism. While criticizing the nationalistic centralized narrative and exploring the different dimensions of human experience, the anti-nationalist critique tends to discard the notion of universality, truth and social justice; without those concepts, historical knowledge becomes mere intellectual enterprise. History is not only the study of the past but also essential to our intellect and emotion, and our action in the world. Argument over different historical perspectives is insufficient if it only remains as plain explanation and comparison.